Effects of wave exposure on population and reproductive phenology of an algal turf, Gelidium pusillum (Gelidales, Rhodophyta), Songkhla, Thailand (ScienceDirect, 2016)
The effect of wave exposure on the population and reproductive phenology of the common red alga, Gelidium pusillum (Stackhouse) Le Jolis, was investigated between July 2003 and June 2004, at Suan Song Tha Le, Songkla Province, Thailand. Lengths of thalli, percentage cover, percentage of reproductive fronds and the number of reproductive structures were examined monthly in relation to different degrees of wave exposure (sheltered vs. exposed), temperature, rainfall, day length and tidal cycles. Frond length and percentage cover of G. pusillum were different among sites and seasons. Shorter fronds were found on the exposed shore which had a greater percentage cover. Fronds bleached and died off during the summer months (April and May), which resulted in shorter fronds and reduced percentage cover in June. The thalli reproduced throughout the year, with a predominance of tetrasporophytes. The highest percentage of tetrasporic fronds was 33% in February 2004 and 13% of cystocarpic fronds in April 2004, but male gametophytic fronds were never observed. Rainfall showed a strongly negative influence on reproduction since no reproductive fronds were observed during the rainy season (R2 = 0.49, P = 0.01). The dominance of G. pusillum at this study site and throughout elsewhere in turf habitats might be a function of persistent vegetative growth, densely clumped, and the ability to reproduce almost throughout the entire year.